BIOLOGICAL STUDIES (BIOLOGICHESKIE RABOTY) - Korotkevich,V. S. (1968)
Biological studies conducted on the Antarctic shelf by the 8th Ob' expedition in 1962 and 1963 are described. A list of ichthyological stations gives information on equipment used in sampling, location, depth, time, and quantity and quality of catches. A similar list provides information about the plankton inhabiting the given Antarctic area. Trans. of Sovetskaya Antarkticheskaya Ekspeditsiya. Trudy (USSR) n51 p125-40 1967, by M. Slessers.